The correlation between early or late natural menopausal age and muscle mass percentage and bone mass percentage in postmenopausal women - Jiaoling LUO; Weisen ZHANG; Zhihao CHAI; Feng ZHU; Tong ZHU; Yali JIN; Jing PAN; Chaoqiang JIANG (Zhongguo gonggong weisheng)
ObjectiveTo analyze the correlation between early or late natural menopausal age and muscle mass percentage and bone mass percentage in postmenopausal women, and to provide a reference for health care of postmenopausal women. MethodsA total of 2 059 naturally menopausal women were selected from the Guangzhou Chronic Disease Prospective Cohort Study of Middle-aged and Elderly People. Baseline survey data were collected from November 2017 to January 2020, including general demographic characteristics, female physiological data, and body composition indicators such as muscle mass percentage and bone mass. Generalized linear models were used for data analysis. ResultsThe average age and average menopausal age of the participants were (59.1±5.1) years and (50.4±2.9) years, respectively. After adjusting for relevant confounding factors, compared with the normal menopausal age group, both the early menopausal age group (β=–1.02, 95%CI: –1.83 to –0.21) and the late menopausal age group (β=–0.75, 95% CI: –1.43 to –0.06) were associated with decreased muscle mass percentage (both P values <0.05). No association was found between early or late menopausal age and bone mass percentage. ConclusionsEarly or late natural menopause is associated with decreased muscle mass percentage in postmenopausal women, but not with bone mass percentage.